Factors Influencing the Adoption of Mobile Banking: Perspective Bangladesh - Liza, Farhana Yasmin (Global Disclosure of Economics and Business, 2014)
With the convergence of banking services and mobile technologies, users are able to conduct banking services at any place and at any time through mobile banking. This research examines the factors influencing the adoption of mobile banking in Bangladesh, with a special focus on trust, perceived cost and perceived risk including the facets of perceived risks: performance risk, security/privacy risk, time risk, social risk and financial risk. The research model includes the original variables of extended technology acceptance model (TAM2). Data for this study was collected through a structured questionnaire survey in townships around Dhaka. The research has found that customers will consider adopting mobile banking as long as it is perceived to be useful and easy to use. But the most critical factor for the customer is cost; the service should be affordable. Trust was found to be significantly negatively correlated to perceived risk. Thus, trust plays a role in risk mitigation and in enhancing customer loyalty.